NATUVATION - NATURE' INNOVATION (CIPEEX, 2022)
IT IS NOTORIOUS THAT OVER TIME THE ENVIRONMENT HAS BEEN DEGRADING MORE AND MORE WITH EACH PASSING YEAR. THE GREAT RESPONSIBLE FOR THIS IS THE HUMAN BEING, WHO WITH HIS GREAT THIRST FOR DOMINATING NATURE AND GETTING MORE AND MORE POWER, HAS BEEN CARRYING A GREAT MASS OF DESTRUCTION, CAUSING NATURAL DISASTERS THAT DEGRADE THE PLANET LITTLE BY LITTLE, LIKE THE GLOBAL WARMING. WITH THIS IN MIND, NATUVATION WAS PLANNED, AN ATTEMPT TO MAKE PEOPLE AWARE OF THEIR OWN ACTIONS.
Keywords: environment; Lean Inception; awareness; software engineering